Pendampingan Perencanaan Pembuatan Talud Pengaman Pantai di Desa Patande Kecamatan Wawonii Timur Laut Kabupaten Konawe Kepulauan - Hasina, Hado -; Hawa, Sitti; Mahdar, Mahdar; Satyadharma, Maudhy; Assegaf, Muhammad; Razinati, Siti (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Abstract This Community Service activity is directed to implement and apply theories related to civil engineering in accordance with the problems and needs of the community at the location of the activity. The participants in this service activity were Lecturers and Students of the Faculty of Engineering, Civil Engineering Study Program, University of Southeast Sulawesi. The implementation of the activity was carried out in Patande Village, Northeast Wawonii District, Konawe Islands Regency. The results of this Community Service Activity resulted in a design drawing for the construction of a coastal safety liner which is expected to be a valuable input, especially for the Patande Village Government in planning the construction of a Coastal Safety Gathering from abrasion which will threaten the safety of the community. The implementation of Community Service Activities can take place as planned because of the effectiveness of interpersonal communication built by each team member as well as the involvement and empowerment of the community in the activities which carried out.